Służba ideologii i ideologia służby w pamiętnikach działaczy polskiego ruchu narodowego na Śląsku Cieszyńskim sprzed końca I wojny światowej - Szkaradnik, Katarzyna (Górnośląskie Studia Socjologiczne. Seria Nowa, 2021)
In her article, Katarzyna Szkaradnik analyses the memoirs of the pioneers of the Polish national movement in the area of Cieszyn Silesia, and also the memoirs of subsequent social, cultural, and educational activists written before the end of World War I. Szkaradnik examines these texts by focusing on the representations of the idea which the authors were spokesmen for, i.e., Polishness as a cultural legacy as well as Poland as a promised land where the people of Cieszyn Silesia will gain due rights. The metaphors “awakening” and “rebirth” naturalized the bond between these people and Polishness, which was supposed to last thanks to, among other things, Polish religious publications, despite Silesia’s separation from so-called Motherland. In this respect, the memoirs have persuasive-didactic functions in that they help to build and strengthen the national identity. Szkaradnik examines the rhetorical strategies used by the activists (and scholars) of the said movement as well as the system of values which they propagate. The fact of the national activists’ being servants of an ideology is accompanied by their ideology of service, akin to the positivist idea of educational and economic work. Importantly, most of the authors descended from local people of humble origin and they gave up on the chance of social advancement in order to help their countrymates to attain social, political, and intellectual emancipation.